Direitos fundamentais e mutação constitucional - Meinberg, Marcio Ortiz (2014)
The purpose of this work is to analyze the relationship between the Fundamental Rights and the informal constitutional alterations. These alterations on the sense of the Constitution, without changing its text, are known by the doctrine as the Constitutional Mutation. It is a phenomena arising from a set of features found into the Brazilian Constitution of 88 and its norms (supremacy, normative strength and flexibility of the norms). The Fundamental Rights norms also feature some characteristics (structured as Principles, openness and language full of non-legal concepts, whose meanings are quite inaccurate, its synthetic character and the gaps and omissions) which boost the incidence of the constitutional mutation. Beyond that, the Fundamental Rights play a important role related to some situations similar to informal changes to the Constitution, but different from them, as the natural pliability of the Fundamental Rights norms; the influence of the Fundamental Rights the determination of the others constitutional norms (setting the original meaning of these constitutional normative statements); and the transformations performed by the Fundamental Rights into the legal system: by setting the meaning of a non-constitutional norm, the sense change of a non-constitutional norm and the exclusion of the non-constitutional norm from the system